Antimicrobial Susceptibility of Acinetobacter calcoaceticus–Acinetobacter baumannii Complex and Stenotrophomonas maltophilia Clinical Isolates: Results From the SENTRY Antimicrobial Surveillance Program (1997–2016) - Gales, Ana C; Seifert, Harald; Gur, Deniz; Castanheira, Mariana; Jones, Ronald N; Sader, Helio S (Open forum infectious diseases, 2019)
Abstract Background Acinetobacter calcoaceticus–A. baumannii (Acb) complex and Stenotrophomonas maltophilia represent frequent causes of hospital-acquired infections. We evaluated the frequency and resistance rates of Acb complex and S. maltophilia isolates from medical centers enrolled in the SENTRY Program. Methods A total of 13 752 Acb complex and 6467 S. maltophilia isolates were forwarded to a monitoring laboratory by 259 participating sites from the Asia-Pacific region, Latin America, Europe, and North America between 1997 and 2016. Confirmation of species identification and antimicrobial susceptibility testing were performed using conventional methods and/or matrix-assisted laser desorption ionization–time of flight mass spectrometry and the broth microdilution method, respectively. Antimicrobial susceptibility results were interpreted by CLSI and EUCAST 2018 criteria. Results Acb complex and S. maltophilia were most frequently isolated from patients hospitalized with pneumonia (42.9% and 55.8%, respectively) and bloodstream infections (37.3% and 33.8%, respectively). Colistin and minocycline were the most active agents against Acb complex (colistin MIC50/90, ≤0.5/2 mg/L; 95.9% susceptible) and S. maltophilia (minocycline MIC50/90, ≤1/2 mg/L; 99.5% susceptible) isolates, respectively. Important temporal decreases in susceptibility rates among Acb complex isolates were observed for all antimicrobial agents in all regions. Rates of extensively drug-resistant Acb complex rates were highest in Europe (66.4%), followed by Latin America (61.5%), Asia-Pacific (56.9%), and North America (38.8%). Among S. maltophilia isolates, overall trimethoprim-sulfamethoxazole (TMP-SMX) susceptibility rates decreased from 97.2% in 2001–2004 to 95.7% in 2013–2016, but varied according to the geographic region. Conclusions We observed important reductions of susceptibility rates to all antimicrobial agents among Acb complex isolates obtained from all geographic regions. In contrast, resistance rates to TMP-SMX among S. maltophilia isolates remained low and relatively stable during the study period.